Interlaboratory test performance of a portable fiber tester - Quispe Peña, Edgar Carlos (2019)
The objective of this research was to construct and to evaluate a portable fiber tester (PFT) for field test use. The standard wool top (SWT) samples were used for evaluation measurement of fiber diameter using PFT comparatively in three laboratories without restricted temperature or humidity controls. Linear model with three factors was used to derive the least square means and variance components were also determined. In addition, precision and accuracy were determined. The PFT is constructed to be compact and lightweight. It works using digital image technology and can evaluate the fiber diameter for each sample in 45 seconds. The results show that the average fiber diameter measured by PFT at all labs are within IWTO defined tolerance values with a high precision. There were no significant lab effect whereas, variance of labs remained low. It can be concluded that PFT is an instrument with high precision and accuracy to measure the fiber diameter of wool, which may be operated in differing conditions.